Collaborative Learning Effectiveness in Thai Classrooms: A Cultural Psychology Perspective - Abdulhafiz Hile (Advances in Psychological Sciences and Applications, 2026)
Collaborative learning has been widely recognized as an effective pedagogical approach for enhancing student engagement, critical thinking, and academic achievement. However, its effectiveness may vary across cultural contexts. This study examines the effectiveness of collaborative learning in Thai classrooms through a cultural psychology perspective. Drawing on sociocultural theory and cultural dimensions, the study explores how collectivist values, power distance, and interpersonal norms influence students’ participation, interaction, and learning outcomes in group-based learning environments. A mixed-method approach was employed, combining survey data from 280 secondary and undergraduate students with classroom observations and interviews. The findings indicate that collaborative learning is generally effective in promoting engagement and social cohesion, but its impact on critical thinking and individual accountability is moderated by cultural factors. Students tend to prioritize harmony and group consensus, which may limit open disagreement and deep cognitive conflict. The study contributes to the literature by contextualizing collaborative learning within Southeast Asian cultural settings and offers practical implications for designing culturally responsive pedagogy.